Identification of anti-HIV compounds in Helichrysum species (Asteraceae) by means of NMR-based metabolomic guided fractionation - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.